Urothelial genotoxicity of household chemicals in healthy canine urinary bladder organoids relative to observed urinary exposures in pet dogs - Peterson, Hannah M.; Zdyrski, Christopher; Allenspach, Karin; Mochel, Jonathan P.; Trepanier, Lauren A. (Frontiers in Veterinary Science, 2025)
IntroductionUrothelial carcinoma (UC) in pet dogs closely resembles human muscle-invasive UC, which is associated with environmental chemical carcinogens. The aim of this study was to determine whether urinary concentrations of the bladder carcinogens acrolein, inorganic arsenic, and 2,6-dimethylaniline (2,6-DMA) reach genotoxic concentrations in pet dogs with and without UC.MethodsWe first established thresholds for DNA damage from these chemicals using a novel in vitro organoid model. Healthy canine urinary bladder organoids were exposed to acrolein, sodium arsenite, and 2,6-DMA in vitro and we used the alkaline CometChip assay without and with the enzyme Fpg (formamidopyrimidine [fapy]-DNA glycosylase) to measure DNA strand breaks and oxidative DNA damage.ResultsFor acrolein, we found a genotoxic threshold of 20 uM for combined DNA strand breaks and oxidative DNA damage. These findings suggest potentially genotoxic urinary acrolein exposures in 20% of pet dogs (15 of 74) previously surveyed, with no differences between cases and controls. For inorganic arsenic, we observed genotoxicity at 20 uM in canine organoids; none of 74 pet dogs reached this urinary concentration when assayed at a single time point. For 2,6-DMA, the genotoxic threshold was 0.01 uM for combined DNA strand breaks and oxidative DNA damage. Among dogs previously surveyed, 8% of UC cases (3 of 37) and none of 36 controls reached this threshold (p = 0.07).ConclusionAcrolein and 2,6-DMA could reach genotoxic urinary concentrations after household exposures in some pet dogs, and the role of 2,6-DMA in canine bladder cancer risk deserves assessment in a larger sample size.